Multicenter Evaluation of a Novel Immunochromatographic Test for Anti-aspergillus IgG Detection - Piarroux, Raphaël P.; Romain, Thomas; Martin, Aurélie; Vainqueur, Damien; Vitte, Joana; Lachaud, Laurence; Gangneux, Jean-Pierre; Gabriel, Frédéric; Fillaux, Judith; Ranque, Stéphane (Frontiers in Cellular and Infection Microbiology, 2019)
Aspergillus sp. fungi cause various diseases in both immunocompetent and immunocompromised patients. The most frequent Aspergillus disorders include chronic pulmonary aspergillosis (CPA), a life-threatening disease that affects at least 3 million people worldwide, and allergic bronchopulmonary aspergillosis (ABPA), which affects approximately 4.8 million severe asthmatic patients globally. Diagnosis of such diseases involves IgG serological testing; however, the currently available anti-Aspergillus IgG detection assays are inappropriate for resource-poor laboratory settings, as they are expensive, rely on automated procedures, and require stable electrical power. Therefore, accurate CPA or ABPA diagnosis facilities are lacking in most low- and middle-income countries. We evaluated a novel anti-Aspergillus antibody immunochromatographic test (ICT) that requires minimal laboratory equipment. Two evaluations were performed: a single-center 4-month prospective study in a French reference laboratory (44 cases/257 patients) and a retrospective study in five French reference laboratories (262 cases and 188 controls). We estimated the ICT indices for the diagnosis of chronic aspergillosis, and the test results were compared to those of anti-Aspergillus IgG immunoblot (IB) assay. Of the 713 patients included in the study, 306 had chronic aspergillosis. Test sensitivity and specificity were 88.9% (95%CI[85–92]) and 96.3% (95%CI[94–98]) for the ICT and 93.1% (95%CI[90–96]) and 94.3% (95%CI[92–96]) for the IB, respectively. Agreement between the two assays was almost perfect (kappa = 0.86). As this ICT displays good diagnostic performance and complies with the ASSURED (Affordable, Sensitive, Specific, User-friendly, Equipment-free, and Delivered) criteria, we concluded that this anti-Aspergillus antibody ICT can be used to diagnose Aspergillus diseases in resource-poor settings.